Rekonstruksi Fikih Munakahat untuk Menghadapi Toxic Masculinity dalam Rumah Tangga: Analisis QS. Al-Baqarah Ayat 233 - Hamdi, Saibatul; Maulidi, Ahmad Riyadh (MAHAKIM Journal of Islamic Family Law, 2025)
The phenomenon of toxic masculinity emerges from misinterpretations of masculinity, particularly within the context of household relations. The view that positions men as superior and women as secondary has generated unequal relational practices that contradict the principles of gender justice in Islam. This article aims to analyze QS. Al-Baqarah verse 233 as a theological basis for re-examining the concept of nafāqah (financial and non-financial support) and gender relations in Islamic jurisprudence, as well as to assess the extent to which this verse can serve as a counter-narrative to toxic masculinity. This research employs a qualitative approach through library research using the thematic exegesis (tafsīr maudhu‘ī) method, combined with content and comparative analysis of classical and contemporary exegetical works and relevant fiqh literature. The findings reveal three key points: (1) the social construction that places women as a secondary gender contributes to the marginalization of domestic roles that are, in fact, essential; (2) the categorization of masculine–feminine traits is often based on flawed cultural constructs, leading to the legitimization of toxic masculinity; (3) Qur’an Surah Al-Baqarah verse 233 emphasizes a comprehensive notion of nafāqah, which includes material, emotional, and service-based responsibilities of husbands, particularly during childbirth and breastfeeding periods. These findings highlight that the verse offers a paradigm of participatory and service-oriented leadership rather than domination. This article provides conceptual implications for developing a more gender-equitable Islamic discourse and for reconstructing household relations free from toxic masculinity.